Progress in drug delivery system for fibrosis therapy - Lei Xing; Xin Chang; Lijun Shen; Chenglu Zhang; Yatong Fan; Chongsu Cho; Zhiqi Zhang; Hulin Jiang (Elsevier, 2021)
Fibrosis is a necessary process in the progression of chronic disease to cirrhosis or even cancer, which is a serious disease threatening human health. Recent studies have shown that the early treatment of fibrosis is turning point and particularly important. Therefore, how to reverse fibrosis has become the focus and research hotspot in recent years. So far, the considerable progress has been made in the development of effective anti-fibrosis drugs and targeted drug delivery. Moreover, the existing research results will lay the foundation for more breakthrough delivery systems to achieve better anti-fibrosis effects. Herein, this review summaries anti-fibrosis delivery systems focused on three major organ fibrotic diseases such as liver, pulmonary, and renal fibrosis accompanied by the elaboration of relevant pathological mechanisms, which will provide inspiration and guidance for the design of fibrosis drugs and therapeutic systems in the future.